Art Teachers' Attitudes Toward Online Learning: An Empirical Study Using Self Determination Theory - Wang, Mo; Wang, Minjuan; Cui, Yulu; Zhang, Hai (Frontiers in Psychology, 2021)
The pandemic in 2020 made online learning is one of the widely used modality of teaching in several countries and it has also entered the spotlight of educational research. become a central issue in educational research, especially during this current pandemic. However, online learning has always been a challenge for disciplines (engineering, biology, and art) that require hands-on practice. For art teachersteaching or training, online learning has many advantages and disadvantages. How art teachers embrace and adapt their teaching for online delivery remains an unanswered question. This research focuses onexamines 892 art teachers’ attitudes towards online traininglearning they accepted, consideringusingon the learning environment, motivation, mental engagement, and behavior as predictors. of 892 art teachers’ attitudes toward online learning, using sStructural equation modeling was used to explore the relationship between these four elements during these teachers’ participation in an online learning program. The results reveal significant correlations between the learning environment, motivation, mental engagement, and behavior. , thus supporting our research hypothesis. Moreover, this study reveals the group characteristics of art teachers, also have particular group characteristics, which can actually be supported by online learning programs. These findings help us better understandprovide insights into how art teachers view and use online learning they accepted, and thus can contribute toshed lights on their professional development.